Cash and Corporate Control - FALEYE, OLUBUNMI (Journal of Finance, 2004)
ABSTRACT The takeover market is often suggested as appropriate for containing the agency problems of excessive corporate cash holdings. However, recent studies report contradictory evidence. I focus on the takeover‐deterrence effects of corporate liquidity and suggest the proxy contest as an effective alternative control mechanism. I find that proxy fight targets hold 23% more cash than comparable firms, and that the probability of a contest is significantly increasing in excess cash holdings. Proxy fight announcement return also is positively related to excess cash. Following a contest, executive turnover and special cash distributions to shareholders increase, while cash holdings significantly decline.